THE EFFECTIVENESS OF SHARED GOVERNANCE MODELS IN IMPROVING NURSE ENGAGEMENT AND PATIENT OUTCOMES - Ahmed Hamed Abdallh Almuhmmed, Dahba Salem Bashir, Hailah Rashed Saud Aldosari, Haya Fahd Hamad Al Dosari, Hanan Hamdan Shadad Alharbi, Haya Saad Hamdan Aldosari, Ohoud Suliman Alotibi, Amani Abass Alsabban, Abdullah Hamad Alsulami,; Ali Mohammed Ahmed Alqassmi, Zainab Haidar Alsharfa, Mosaad Sayer Alruwaily, Munayfah Eid Alruwaili, Ali Abdalaziz Ibrahim Alrayes (Chelonian Research Foundation, 2022)
While it is well recognized that management and the culture of the healthcare setting may hinder the adoption of evidence-based practice, there is a lack of comprehensive research about the particular impact and assistance provided by nurse leaders in this regard. This integrated study seeks to examine the impact of nursing leadership on the implementation of evidence-based practice in modern healthcare environments. The researchers conducted an integrated literature review, examining a total of 28 articles. The study used three databases: PubMed, CINAHL, and the Cochrane Library, covering the period from 2006 to 2016. The primary importance of leadership, the approach used, and the identification and resolution of obstacles or enablers in implementing evidence-based practice were identified as crucial factors. Nurse managers play a crucial role in facilitating the adoption of evidence-based practice by creating a culture and environment that supports its implementation. In order to accomplish this, individuals must possess a foundational understanding and be cognizant of and overcome obstacles to execution. Additionally, they must comprehend the pivotal job of nurse managers in establishing and fostering the most favorable setting. Keywords: governance models, nurse engagement, patient outcomes, review, nurse managers.